2011
DOI: 10.1007/s12079-011-0138-y
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate sensitizes Tamoxifen action in ER-α positive breast cancer cells

Abstract: It is estimated that one in eight women will be affected with cancer during their lives, which means over 1 million women worldwide will be diagnosed with breast cancer in the year of 2011. Roughly, 70% of breast cancer will be estrogen receptor-alpha (ER-α) positive. The presence of ER-α is associated with better prognosis and is able to determine if tumors will respond to the estrogen-blocking/ER-antagonist drug Tamoxifen (TAM). However, a significant fraction of ER-positive tumors respond with minimal or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…At standard dosages, Tam has minimal or no effect on Tam-resistant breast cancer cells (27). At higher concentrations of Tam beyond the dose that promotes tumor growth The level of Gαѕ was reduced to <50% of the control levels in the cells transfected with oligos specific for Gαѕ.…”
Section: Discussionmentioning
confidence: 96%
“…At standard dosages, Tam has minimal or no effect on Tam-resistant breast cancer cells (27). At higher concentrations of Tam beyond the dose that promotes tumor growth The level of Gαѕ was reduced to <50% of the control levels in the cells transfected with oligos specific for Gαѕ.…”
Section: Discussionmentioning
confidence: 96%
“…Quite a few reports have presented a plausible explanation for endocrinal breast cancer therapy in post-menopausal women where a non-significant response to estrogen receptor-positive MCF-7 breast tumors was observed. PoMx exhibiting anticancer properties were successfully tested at a concentration of 300 mg/ml in combination with 1 mM tamoxifen to sensitize and enhance the activity of the latter, thereby inhibiting resistant MCF-7 cell proliferation (Aiyer et al, 2012;Banerjee et al, 2011).…”
Section: Breast Cancermentioning
confidence: 99%
“…Subsequently, it was demonstrated that pomegranate fruit extracts enhance the action of the anti-estrogen tamoxifen in breast cancer cells [9]. Polyphenols also inhibit the expression of genes codifying for key androgen-synthesizing enzymes and androgen receptors [10] and EA was found to affect the growth, motility and invasiveness of androgen-independent prostate cancer [11].…”
Section: Introductionmentioning
confidence: 99%